7(x-6)=5(x+2)

Simple and best practice solution for 7(x-6)=5(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-6)=5(x+2) equation:


Simplifying
7(x + -6) = 5(x + 2)

Reorder the terms:
7(-6 + x) = 5(x + 2)
(-6 * 7 + x * 7) = 5(x + 2)
(-42 + 7x) = 5(x + 2)

Reorder the terms:
-42 + 7x = 5(2 + x)
-42 + 7x = (2 * 5 + x * 5)
-42 + 7x = (10 + 5x)

Solving
-42 + 7x = 10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-42 + 7x + -5x = 10 + 5x + -5x

Combine like terms: 7x + -5x = 2x
-42 + 2x = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-42 + 2x = 10 + 0
-42 + 2x = 10

Add '42' to each side of the equation.
-42 + 42 + 2x = 10 + 42

Combine like terms: -42 + 42 = 0
0 + 2x = 10 + 42
2x = 10 + 42

Combine like terms: 10 + 42 = 52
2x = 52

Divide each side by '2'.
x = 26

Simplifying
x = 26

See similar equations:

| 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 |

Equations solver categories